Advancements in research on the cardiovascular toxicity caused by TEC family kinases inhibitors - Zhang, Yi; Fu, Huangxi; Kang, Xingchen; Qiu, Zixuan; Yan, Hao; He, Qiaojun; Yang, Bo; Xu, Zhifei; Luo, Peihua (Frontiers in Pharmacology, 2026)
The tyrosine kinase expressed in hepatocellular carcinoma (TEC) family kinases (TFKs) are a subfamily of non-receptor protein tyrosine kinases (PTKs) that include five members: TEC, bruton’s tyrosine kinase (BTK), interleukin 2-inducible T-cell kinase (ITK/EMT/TSK), bone marrow tyrosine kinase on chromosome X (BMX/ETK), and tyrosine-protein kinase (TXK/RLK). They play key roles in cell signaling and immune regulation. Emerging evidence highlights their involvement in cardiovascular diseases (CVDs) such as ischemic heart disease (IHD), atherosclerosis (AS), sepsis-related dysfunction, atrial fibrillation (AF), myocardial hypertrophy, coronary atherosclerotic heart disease, myocardial infarction (MI), and post-myocardial infarction complications. However, no review has comprehensively addressed the cardiovascular toxicity of TFKs inhibitors. This review provides a comprehensive and systematic analysis of the cardiovascular toxicity profiles of TFK inhibitors (TFKis), focusing on underlying molecular mechanisms, comparing toxicity across different agents and generations, and discussing clinical implications.